Preparation and application of high-entropy lithium argyrodite type sulfide solid electrolyte
The high-entropy lithium silver germanium sulfide solid electrolyte is prepared through multi-site doping and high-temperature heat treatment processes, which solves the problems of stability and high cost of traditional sulfide electrolyte materials and achieves high ionic conductivity and good stability. Electrolyte materials suitable for industrial applications of all-solid-state batteries.
Patent Information
- Application Number
- CN202411417706.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing sulfide solid electrolyte materials have poor chemical stability and are sensitive to water molecules in the air, resulting in limited application in actual battery systems, and the synthesis process is complex and costly.
Multiple -point doping methods are used to prepare high -entropilized lithium sulfur sulfur sulfur sulfide solid electrolytes, improve their chemical and electrochemical stability by introducing specific elements, and improve ion conductivity through high temperature thermal treatment process.
It significantly improves the chemical stability, air stability and electrochemical properties of solid electrolytes, reduces production costs, and achieves high -ion conductivity, suitable for large -scale industrial production.
Smart Images

Figure CN119361806A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid electrolytes, and in particular relates to the preparation and application of a high-entropy lithium argyrodite-type sulfide solid electrolyte. Background Art
[0002] With the rapid development of portable electronic devices, electric vehicles and renewable energy storage systems, the current society has an increasing demand for high-performance, low-cost and long-life battery technology. Although traditional liquid electrolytes can meet the performance requirements of lithium batteries, their inherent safety issues, insufficient low-temperature performance and bottlenecks in the energy density of the entire battery limit their further development. Especially in high-energy-density application scenarios, the flammability and leakage risk of liquid electrolytes are major safety hazards. In addition, the interface stability between the liquid electrolyte and the lithium metal anode is poor, and the uneven lithium deposition leads to the formation of dendrites, which poses a risk of battery short circuit and failure. All-solid-state batteries, because they use solid electrolytes, can theoretically solve the safety problems of liquid electrolytes. They have higher energy density, wider operating temperature range and longer service life, and are widely regarded as an important development direction of future battery technology. Compared with liquid electrolytes, solid electrolytes are non-flammable, have high mechanical strength, and can effectively inhibit the growth of lithium dendrites. However, the key to realizing this technology lies in the development of solid electrolyte materials with high ionic conductivity and good stability.
[0003] Sulfide solid electrolytes have attracted extensive attention in recent years, mainly because of their high —3 ~10 —2 S / cm, which is comparable to the ionic conductivity of liquid electrolytes. In addition, sulfide electrolytes generally have a wide electrochemical window and good mechanical flexibility, which allows them to form good interfacial contact when matched with electrode materials. However, traditional sulfide solid electrolytes have poor chemical stability and are extremely sensitive to water molecules in the air. This instability not only limits its application in practical battery systems, but also increases the preparation and processing costs of the materials. In addition, the synthesis process of such materials is complicated, usually involving high-temperature sintering or expensive raw materials, which further increases their production costs.
[0004] Introducing the concept of high entropy materials in the design of sulfide solid electrolytes can effectively overcome the above challenges. High entropy materials form a highly disordered crystal structure through the uniform mixing of multiple elements. High entropy sulfide materials, especially high entropy lithium argyrodite-type structures, can effectively maintain high ionic conductivity while enhancing their chemical and electrochemical stability due to their unique structural disorder. In addition, by introducing specific elements to improve their tolerance to water molecules in the air, their stability in practical applications can be significantly improved.
[0005] Another significant advantage of high-entropy materials is their stability at the battery interface. In solid-state batteries, the interfacial stability between the electrolyte and the electrode material is crucial to the electrochemical performance of the entire battery. Due to the diversity of their composition and the complexity of their structure, high-entropy sulfides can form a more uniform and stable SEI layer at the interface, hindering the further decomposition of the electrolyte, which is of great significance for improving interfacial stability.
[0006] In short, the research and development of sulfide solid electrolyte materials based on high entropy lithium argyrodite structure can not only significantly improve the overall performance of all-solid-state batteries, but also help promote the large-scale popularization of all-solid-state battery technology in practical applications. The success of this innovative technology will provide key technical support for the next generation of high-safety, high-energy-density energy storage systems, with broad industrial application prospects and significant social and economic benefits. Summary of the invention
[0007] The purpose of the present invention is to prepare a high-entropy lithium argyrodite-type sulfide solid electrolyte with excellent performance to solve the problems existing in the prior art.
[0008] Based on the above objectives, the present invention adopts the following technical solutions:
[0009] The present invention performs multi-site doping according to the different physical properties of elements to prepare a high-entropy lithium argyrodite-type sulfide solid electrolyte with high ionic conductivity, high air stability, stable electrochemical performance and excellent interface stability.
[0010] A high entropy lithium argyrodite-type sulfide solid electrolyte, characterized in that the chemical formula of the solid electrolyte material is:
[0011] Li θ M α N β P 1-α-β S 4.5-λ X λ Y 1.5 ;
[0012] Wherein, M is any two or more of Al, Si, Ge, Ti, and Mn elements, N is any two or more of Mg, Zn, In, Cu, Sn, Bi, and Sb elements, X is any two or more of F, O, N, Se, and Te elements, and Y is any one or more of Cl, Br, and I elements; in the chemical formula, 5.32<θ<6.46, 0.01≤α<0.32, 0.01≤β<0.32, and 0<α+β≤0.32, 0<λ≤0.5.
[0013] The method for preparing the high entropy lithium argyrodite-type sulfide solid electrolyte as described above is characterized by comprising the following steps:
[0014] 1) According to the target chemical formula, the required Li source compound, M source compound, N source compound, X source compound and Y source compound are dried;
[0015] 2) The raw materials dried in step 1) are weighed and mixed according to the molar ratio of the electrolyte chemical formula to obtain a mixed material precursor;
[0016] 3) subjecting the mixed material precursor obtained in step 2) to ball milling and tableting to obtain a sheet precursor;
[0017] 4) The flake precursor obtained in step 3) is subjected to high-temperature heat treatment, cooled to room temperature, and then ground into powder under the protection of an inert atmosphere to obtain a high-entropy sulfide solid electrolyte material.
[0018] Furthermore, in step 1), the Li source compound includes two or more of Li2S, Li3P, Li3N, Li2O, LiF, LiCl, LiBr, and LiI; the M source compound includes two or more of AlF3, Al2O3, AlN, AlCl3, AlBr3, AlI3, SiO2, SiS2, Si3N4, SiSe2, SiTe2, GeO2, Ge3N4, GeSe2, GeTe2, TiO2, TiSe2, TiTe2, MnF2, MnO2, Mn3N2, MnSe, MnTe, MnCl2, MnBr2, and MnI2; the N source compound includes MgF2, MgO, Mg3N2, MgSe, MgTe, MgCl2, MgBr2, MgI2, ZnF2, ZnO, Zn3N2, ZnSe, ZnTe, ZnCl2, ZnBr2, ZnI2, InF3, In2O3, InN, In2Se3, In2Te3, In Cl3, InBr3, InI3, CuF2, CuO, Cu3N2, CuSe, CuTe, CuCl2, CuBr2, CuI2, SnF4, SnO2, Sn3N4, SnCl4, SnSe2, SnTe2, BiF3, Bi2O3, BiN, Bi2Se3, Bi2 Te3, BiCl3, BiBr3, BiI3, SbF3, Sb2O3, Sb2Se3, Sb2Te3, two or more; P source: P, P2S5, P4S9, P4S5, P4S6, one or more; S source: S, Li2S, P2S5, P4S9, P4S5, P4S6, one or more; X source compounds include LiF, AlF3, Al2O3, AlN, SiO2, Si3N4, SiSe2, SiTe2, GeO2, Ge3N4, GeSe2, GeTe2, TiO2, TiSe2, TiTe2, MnF2, MnO2, Mn3N2, MnSe, Two or more of MnTe, MgF2, MgO, Mg3N2, MgSe, MgTe, ZnF2, ZnO, Zn3N2, ZnSe, ZnTe, InF3, In2O3, InN, In2Se3, In2Te3, CuF2, CuO, Cu3N2, CuSe, CuTe, SnF4, SnO2, Sn3N4, SnCl4, SnSe2, SnTe2, BiF3, Bi2O3, BiN, Bi2Se3, Bi2Te3, SbF3, Sb2O3, Sb2Se3, and Sb2Te3; the Y source compound includes one or more of LiCl, LiBr, and LiI.
[0019] Furthermore, the drying treatment in step 1) is carried out under vacuum drying at 60 to 80°C for 10 to 12 hours.
[0020] Furthermore, in the step 2), the mixing after weighing needs to be performed using an agate mortar and ground for 10-20 minutes for mixing.
[0021] Furthermore, in the step 3), the mixed material precursor is subjected to dry ball milling process, using a high-energy ball mill for mixing, the ball mill speed is 400-600 rpm / min, the ball milling time is 8-12 h, the ball-to-material ratio is 20:1, and the mass ratio of large ball milling beads to small ball milling beads is 1:1.
[0022] Furthermore, in the step 3), the mixed material precursor is subjected to tableting after ball milling, and the pressure is 200-400 MPa, the diameter of the sheet precursor is 10 mm, and the mass is 500-1000 mg.
[0023] Furthermore, the high temperature treatment process conditions of the flake precursor in step 4) include: heat treatment temperature 400-600 °C, heat treatment time 6-8 h, heating rate 1-5 °C / min; the cooling rate to room temperature is 10-20 °C / min.
[0024] According to the application of the high entropy lithium argyrodite-type sulfide solid electrolyte material prepared by the method as described above, the solid electrolyte material is applied to an all-solid-state lithium battery.
[0025] Furthermore, the all-solid-state lithium battery includes a composite positive electrode layer, a sulfide electrolyte layer and a lithium negative electrode / composite negative electrode layer.
[0026] The composite positive electrode layer and the sulfide electrolyte layer contain the high-entropy lithium argyrodite-type sulfide solid electrolyte material obtained by the above-mentioned preparation process.
[0027] The application advantages of the high entropy lithium argyrodite-type sulfide solid electrolyte material co-doped with cations and anions of the present invention are as follows:
[0028] 1) By introducing heterovalent metal cations into the argyrodite-type sulfide electrolyte, additional lithium vacancies can be generated in the structure, significantly increasing the lithium ion carrier concentration, increasing the freedom of lithium ion migration, optimizing the migration path of lithium ions, and improving the ionic conductivity of the electrolyte body;
[0029] 2) Introducing soft acid cations into the argyrodite-type sulfide electrolyte can promote the soft base S in the structure to form a strong covalent bond with it, thereby forming a structurally stable tetrahedron. When in contact with water molecules in the air, the combination of the soft base S element and the H element is effectively inhibited, thereby protecting the structural stability of the sulfide electrolyte and improving the air stability;
[0030] 3) Doping inorganic anions in argyrodite-type sulfide electrolytes can improve the interface stability between the electrolyte and lithium metal. During the cycle, a stable interface layer is formed in situ between the electrolyte and lithium metal, which hinders the contact between the sulfide electrolyte and lithium metal, further inhibits the side reactions at the interface, protects the structure of the sulfide electrolyte, and improves the stability of the lithium metal negative electrode interface;
[0031] 4) Introducing a variety of halogen anions into argyrodite-type sulfide electrolytes can increase the configuration entropy of the material. By adjusting the types of halogen ions inside the structure, the disorder of the anions can be increased. The mixed arrangement of anions increases the disorder of the structure, affects the sublattice near the lithium ions, reduces the diffusion energy barrier of lithium ions, and further improves the ionic conductivity of the sulfide.
[0032] The preparation method of the high-entropy lithium argyrodite-type sulfide electrolyte material provided by the present invention is a dry process, which has the advantages of safety and environmental protection compared with the wet process, and avoids the use of organic solvents to reduce production costs.
[0033] The high-entropy lithium argyrodite-type sulfide electrolyte prepared by the high-temperature heat treatment process of the present invention has extremely high ionic conductivity, can meet the use requirements of most batteries, and has a simple preparation process and low raw material cost. At the same time, the output of the electrolyte material is high and is suitable for large-scale industrial mass production. It has broad application prospects and is of great significance to the development of all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings in the embodiments of the present invention are briefly introduced below.
[0035] Figure 1 This is the SEM morphology of Example 1;
[0036] Figure 2 is the XRD characteristic spectrum of Example 1;
[0037] Figure 3 is an impedance curve diagram of Example 1;
[0038] Figure 4 is a full battery cycle diagram of Example 1;
[0039] Figure 5 This is a statistical diagram of H2S release in Example 1;
[0040] Figure 6 It is the SEM morphology image of comparative example 1;
[0041] Figure 7 It is the XRD characteristic spectrum of comparative example 1;
[0042] Figure 8It is the impedance curve diagram of comparative example 1;
[0043] Fig. 9 It is the full battery cycle diagram of comparative example 1;
[0044] Fig.10 This is a statistical chart of H2S release in Comparative Example 1. DETAILED DESCRIPTION
[0045] The present invention provides a preparation process and application of a high entropy lithium argyrodite-type sulfide electrolyte material. In order to further clarify the purpose and technical solution of the present invention, the present invention is described in detail in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention, nor can they be understood as limiting the scope of protection of the present invention.
[0046] The present invention adopts the strategy of co-doping of cations and anions to prepare a high-entropy lithium argyrodite-type sulfide solid electrolyte material, the chemical formula of which is Li θ M α N β P 1-α-β S 4.5-λ X λ Y 1.5 , wherein 5.32<θ<6.46, 0.01≤α<0.32, 0.01≤β<0.32 and 0<α+β≤0.32, 0<λ≤0.5. The electrolyte material has high ionic conductivity, high air stability, stable electrochemical performance and excellent interface stability.
[0047] Example 1
[0048] Example 1 of the present invention provides a preparation process of a high entropy lithium argyrodite-type sulfide solid electrolyte material, the structural formula of which is Li 5.9 Al 0.05 Si 0.05 Ge 0.05 Mg 0.05 Zn 0.05 In 0.05 P 0.7 S 4.05 F 0.25 O 0.15 N 0.05 Cl 0.5 Br 0.5 I 0.5 , the specific implementation process is as follows:
[0049] The raw materials Li2S, LiCl, LiBr, LiI, P2S5, AlN, SiS2, GeO2, MgF2, ZnO, and InF3 were dried at 60 °C for 10 h in a vacuum oven, and then the mass of the raw materials was calculated according to the molar ratio of the chemical formula under the protection of an inert atmosphere. After weighing, they were ground in an agate mortar for 10 min, and then placed in a zirconia ball mill, and ball milled for 8 h at 600 rpm / min using a planetary high-energy ball mill, with a ball-to-material ratio of 20:1. Under the protection of an inert atmosphere, 600 mg of the ball-milled mixed material precursor was weighed and placed in a mold, pressed into a 10 mm disc at a pressure of 300 MPa, and then sealed in a quartz tube containing an inert gas, and subjected to a high-temperature heat treatment at 500 °C for 6 h in a muffle furnace, with a heating rate controlled at 5 °C / min, and then cooled to room temperature at a cooling rate of 20 °C / min, and finally ground into powder under the protection of an inert atmosphere to obtain Li 5.9 Al 0.05 Si 0.05 Ge 0.05 Mg 0.05 Zn 0.05 In 0.05 P 0.7 S 4.05 F 0.25 O 0.15 N 0.05 Cl 0.5 Br 0.5 I 0.5 High entropy lithium argyrodite-type sulfide electrolyte.
[0050] Figure 1 This is a SEM morphology of the high-entropy lithium argyrodite-type sulfide electrolyte prepared in Example 1. Through observation, it can be found that the particle size is about 10 μm. Figure 2 : is the XRD spectrum of the sulfide electrolyte in Example 1, which is a typical argyrodite-type sulfide with a cubic crystal structure of the F-43m space group. The electrochemical test contents of the argyrodite-type sulfide electrolyte in this Example 1 are as follows:
[0051] 1) Test of ionic conductivity and activation energy: Under the protection of inert gas, 200 mg of the sulfide electrolyte powder prepared in Example 1 was weighed and placed in a special solid-state battery mold, and pressurized at a pressure of 300 MPa. Then, a variable temperature AC impedance spectrum test was performed using a power transmission electrochemical tester. The ionic conductivity and activation energy of the sulfide solid electrolyte in Example 1 were calculated according to the obtained impedance value and the Arrhenius formula, and the calculation results are shown in Table 1. At the same time, the configuration entropy of the high-entropy lithium argyrodite-type sulfide solid electrolyte in Example 1 was calculated according to the thermodynamic formula, and the calculation results are shown in Table 1. It can be found that the configuration entropy of the sulfide electrolyte prepared in Example 1 is 1.54 R (>1.5 R), which meets the characteristics of high-entropy materials, and its ionic conductivity is as high as 11.2 mS / cm.
[0052] 2) Test of electrochemical performance: Under the protection of an inert atmosphere, weigh 100 mg of the sulfide electrolyte powder prepared in Example 1, put it into a special solid-state battery mold, and press-form it at a pressure of 200 MPa to obtain a sulfide electrolyte sheet. Weigh the LiCoO2 (LCO) positive electrode active material, the sulfide electrolyte in Example 1, and nanocarbon fiber (VGCF) in a mass ratio of 70:30:1, put them into an agate mortar and grind them for 30 min to fully mix them to form a composite positive electrode material. Weigh 10 mg of the composite positive electrode material and spread it evenly on one side of the sulfide electrolyte sheet, and take a metal lithium foil with a diameter of 7 mm and place it on the other side of the sulfide electrolyte sheet. Apply a pressure of 40 MPa to the entire mold of the solid-state battery to ensure that all parts of the battery fit tightly. The battery cycle performance was tested using a blue electric test system, with a voltage range of 2.8 - 4.2 V (vs. Li / Li + ), the charge and discharge rate is 0.5 C, and the charge and discharge curve of the all-solid-state battery assembled based on Example 1 is as follows Figure 4 It can be found that after 1000 cycles of charge and discharge tests, the capacity retention rate is 66.2%, the discharge specific capacity is as high as 82.2 mAh / g, and the full battery shows good electrochemical stability.
[0053] 3) Air stability test: Under inert atmosphere, weigh 100 mg of the sulfide electrolyte powder prepared in Example 1 and use The 10 mm mold was pressurized at 300 MPa and, after demoulding, placed in a 5 L sealed container to test the release of H2S, where the sealed container contained air with a humidity of 30%. Figure 5 After 2 h of exposure, the H2S release of the sulfide electrolyte in Example 1 is 0.37 cm 3 / g.
[0054] Example 2
[0055] Example 2 of the present invention provides a preparation process of a high entropy lithium argyrodite-type sulfide solid electrolyte material, the structural formula of which is Li 5.98 Al 0.04 Si 0.04 Ge 0.04 Ti 0.04 Mg 0.04 Zn 0.04 In 0.04 Cu 0.04 P 0.68 S 4.1 F 0.2 O 0.12 N 0.04 Se 0.0 4Cl 0.5 Br 0.5 I 0.5 , the specific implementation process is as follows:
[0056] The raw materials Li2S, LiCl, LiBr, LiI, P2S5, AlN, SiS2, GeO2, TiCl4, MgF2, ZnO, InF3, and CuSe were dried at 60 ℃ in a vacuum oven for 10 h. Then, under the protection of an inert atmosphere, the mass of the raw materials was calculated according to the molar ratio of the chemical formula. After weighing, they were ground in an agate mortar for 10 min and then placed in a zirconia ball mill. They were ball milled in a planetary high-energy ball mill at 600 rpm / min for 8 h, with a ball-to-material ratio of 20:1. Under the protection of inert atmosphere, 600 mg of the ball-milled mixed material precursor was weighed and placed in a mold, and pressed into a 10 mm disc at a pressure of 300 MPa, and then sealed in a quartz tube containing an inert gas, and subjected to a high-temperature heat treatment at 500 °C for 6 h in a muffle furnace, with the heating rate controlled at 5 °C / min, and then cooled to room temperature at a cooling rate of 20 °C / min, and finally ground into powder under the protection of inert atmosphere to obtain Li 5.98 Al 0.04 Si 0.04 Ge 0.04 Ti 0.04 Mg 0.04 Zn 0.04 In 0.04 Cu 0.04 P 0.68 S 4.1 F 0.2 O 0.12 N 0.04 Se 0.04 Cl 0.5 Br 0.5 I 0.5High entropy lithium argyrodite-type sulfide electrolyte. The performance test of Example 2 is consistent with that of Example 1. The ionic conductivity and configurational entropy of the sulfide electrolyte prepared in Example 2 are calculated by the formula as shown in Table 1, where the ionic conductivity can reach 11.5 mS / cm, and the configurational entropy ΔS config It is 1.54 R (>1.5 R), which belongs to high entropy electrolyte materials.
[0057] Example 3 Example 3 of the present invention provides a preparation process of a high entropy lithium argyrodite-type sulfide solid electrolyte material, the structural formula of which is Li 6.06 Al 0.04 Si 0.04 Ge 0.04 Ti 0.04 Mn 0.04 Mg 0.04 Zn 0.04 In 0.04 Cu 0.04 Sn 0.04 P 0.6 S 4.02 F 0. 2O 0.16 N 0.04 Se 0.04 Te 0.04 Cl 0.5 Br 0.5 I 0.5 , the specific implementation process is as follows: The raw materials Li2S, LiCl, LiBr, LiI, P2S5, AlN, SiS2, GeO2, TiCl4, MnO2, MgF2, ZnTe, InF3, CuSe, and SnCl4 were dried at 60 ℃ in a vacuum oven for 10 h. Then, under the protection of an inert atmosphere, the mass of the raw materials was calculated according to the molar ratio of the chemical formula. After weighing, they were ground in an agate mortar for 10 min and then placed in a zirconia ball mill. They were ball milled in a planetary high-energy ball mill at 600 rpm / min for 8 h, with a ball-to-material ratio of 20:1. Under the protection of inert atmosphere, 600 mg of the ball-milled mixed material precursor was weighed and placed in a mold, and pressed into a 10 mm disc at a pressure of 300 MPa, and then sealed in a quartz tube containing an inert gas, and subjected to a high-temperature heat treatment at 500 °C for 6 h in a muffle furnace, with the heating rate controlled at 5 °C / min, and then cooled to room temperature at a cooling rate of 20 °C / min, and finally ground into powder under the protection of inert atmosphere to obtain Li 6.06 Al 0.04 Si 0.04 Ge 0.04 Ti 0.04 Mn 0.04 Mg 0.04Zn 0.04 In 0.04 Cu 0.04 Sn 0.04 P 0.6 S 4.02 F 0.2 O 0.16 N 0.04 Se 0.04 Te 0.04 Cl 0.5 Br 0.5 I 0.5 High entropy lithium argyrodite-type sulfide electrolyte. The performance test of Example 3 is consistent with that of Example 1. The ionic conductivity and configurational entropy of the sulfide electrolyte prepared in Example 3 are calculated by the formula as shown in Table 1, where the ionic conductivity can reach 12.6 mS / cm, and the configurational entropy ΔS config It is 1.58 R (>1.5 R), which belongs to high entropy electrolyte materials.
[0058] Comparative Examples 1-3
[0059] Comparative Example 1 (Li 5.5 PS 4.5 Cl 1.5 )、Comparative Example 2(Li 5.5 PS 4.5 Cl 0.8 Br 0.7 ) and Comparative Example 3 (Li 5.5 PS 4.5 Cl 0.5 Br 0.5 I 0.5 ) The preparation process of the sulfide solid electrolyte is the same as that of Example 1-3 except for the use of raw materials. config , ionic conductivity σ and activation energy ΔE are shown in Table 1, wherein the configuration entropy of the comparative examples is less than 1.5 R, which does not meet the basic characteristics of high entropy materials and belongs to medium-low entropy materials. At the same time, the ionic conductivity of the comparative examples is lower than that of the embodiments. Figure 6-10 They are respectively the SEM morphology, XRD characteristic spectrum, impedance spectrum, charge and discharge cycle curve of the all-solid-state battery and H2S release amount diagram of Comparative Example 1. By observing the SEM spectrum, it can be found that the particle size of the sulfide electrolyte in Comparative Example 1 is relatively large (>10 μm). The XRD characteristic spectrum reflects that the sulfide electrolyte in Comparative Example 1 is a cubic crystal structure of argyrodite type. Figure 8 It can be found from the impedance spectrum that the impedance value of the sulfide electrolyte of Comparative Example 1 at 25°C is 35.6 Ω, and its ion conductivity is 5.2 mS / cm calculated by the formula. Compared with Examples 1-3, their electrochemical performances are all reduced. Fig. 9The charge and discharge cycle curve of the all-solid-state battery assembled based on the comparative example shows that after 300 cycles of charge and discharge, its discharge specific capacity decays sharply to only 39.1 mAh / g, indicating that the electrochemical performance of the sulfide electrolyte in comparative example 1 is poor. The release amount of H2S of the sulfide electrolyte in comparative example 1 exposed to air with 30% humidity for 2 h is 1.28 cm 3 / g, which is much higher than the H2S release of the sulfide electrolyte in Example 1 under the same conditions.
[0060] Table 1 Configuration entropy ΔS of sulfide electrolytes config , ionic conductivity and activation energy
[0061]
[0062] In summary, the present invention adopts the strategy of co-doping of cations and anions, and obtains a high-entropy lithium argyrodite-type sulfide solid electrolyte through high-energy ball milling + high-temperature heat treatment process. Based on the theory of hard and soft acids and bases, soft acid cations are introduced to improve the stability of the structure and reduce the sensitivity of the electrolyte to water molecules in the air; heterovalent doping of cations generates additional lithium vacancies inside the structure to improve the ionic conductivity of the electrolyte; inorganic anions are introduced to generate a stable interface layer in situ at the lithium negative electrode, hindering the contact between the electrolyte and the lithium negative electrode and improving the stability of the negative electrode interface; the introduction of halogen anions increases the disorder of anions inside the matrix, increases the configurational entropy of the material, reduces the diffusion energy barrier of lithium ions, and further improves the ionic conductivity of the electrolyte. Therefore, the ionic conductivity of the high-entropy lithium argyrodite-type sulfide solid electrolyte described in the present invention can reach 10 mS cm at room temperature. −1 , the release of H2S is significantly reduced when exposed to air with a humidity of 30%. At the same time, the high-entropy lithium argyrodite-type sulfide solid electrolyte of the present invention can match lithium cobalt oxide layered positive electrode materials and lithium metal / lithium alloy negative electrode materials, and the full battery exhibits excellent charge and discharge performance. The high-entropy lithium argyrodite-type sulfide solid electrolyte of the invention has excellent ionic conductivity and excellent electrochemical stability. At the same time, its preparation process is simple and easy to control, and it is expected to become a sulfide solid electrolyte for commercial and industrial applications.
Claims
1. A high entropy lithium argyrodite-type sulfide solid electrolyte, characterized in that: The chemical formula of the solid electrolyte material is: Li θ M α N β P 1-α-β S 4.5-λ X λ Y 1.5 ; Wherein, M is any two or more of Al, Si, Ge, Ti, and Mn elements, N is any two or more of Mg, Zn, In, Cu, Sn, Bi, and Sb elements, X is any two or more of F, O, N, Se, and Te elements, and Y is any one or more of Cl, Br, and I elements; in the chemical formula, 5.32<θ<6.46, 0.01≤α<0.32, 0.01≤β<0.32, and 0<α+β≤0.32, 0<λ≤0.
5.
2. The method for preparing a high entropy lithium argyrodite-type sulfide solid electrolyte according to claim 1, characterized in that: The following steps are involved: 1) According to the target chemical formula, the required Li source compound, M source compound, N source compound, X source compound and Y source compound are dried; 2) The raw materials dried in step 1) are weighed and mixed according to the molar ratio of the electrolyte chemical formula to obtain a mixed material precursor; 3) subjecting the mixed material precursor obtained in step 2) to ball milling and tableting to obtain a sheet precursor; 4) The flake precursor obtained in step 3) is subjected to high-temperature heat treatment, cooled to room temperature, and then ground into powder under the protection of an inert atmosphere to obtain a high-entropy sulfide solid electrolyte material.
3. The method for preparing the high entropy lithium argyrodite-type sulfide solid electrolyte according to claim 2, characterized in that: In the step 1), the Li source compound includes two or more of Li2S, Li3P, Li3N, Li2O, LiF, LiCl, LiBr, and LiI; the M source compound includes two or more of AlF3, Al2O3, AlN, AlCl3, AlBr3, AlI3, SiO2, SiS2, Si3N4, SiSe2, SiTe2, GeO2, Ge3N4, GeSe2, GeTe2, TiO2, TiSe2, TiTe2, MnF2, MnO2, Mn3N2, MnSe, MnTe, MnCl2, MnBr2, and MnI2; the N source compound includes MgF2 , MgO, Mg3N2, MgSe, MgTe, MgCl2, MgBr2, MgI2, ZnF2, ZnO, Zn3N2, ZnSe, ZnTe, ZnCl2, ZnBr2, ZnI2, InF3, In2O3, InN, In2Se3, In2Te3, InCl3, InBr3, InI3, CuF2, CuO, Cu3N2, CuSe, CuTe, CuCl2, CuBr2, CuI2, SnF4, SnO2, Sn3N4, SnCl4, SnSe2, SnTe2, BiF3, Bi2O3, BiN, Bi2Se3, Bi2Te3 , BiCl3, BiBr3, BiI3, SbF3, Sb2O3, Sb2Se3, Sb2Te3, two or more; P source: one or more of P, P2S5, P4S9, P4S5, P4S6; S source: one or more of S, Li2S, P2S5, P4S9, P4S5, P4S6; X source compounds include LiF, AlF3, Al2O3, AlN, SiO2, Si3N4, SiSe2, SiTe2, GeO2, Ge3N4, GeSe2, GeTe2, TiO2, TiSe2, TiTe2, MnF2, MnO2, Mn3N2, MnSe, Mn Two or more of Te, MgF2, MgO, Mg3N2, MgSe, MgTe, ZnF2, ZnO, Zn3N2, ZnSe, ZnTe, InF3, In2O3, InN, In2Se3, In2Te3, CuF2, CuO, Cu3N2, CuSe, CuTe, SnF4, SnO2, Sn3N4, SnCl4, SnSe2, SnTe2, BiF3, Bi2O3, BiN, Bi2Se3, Bi2Te3, SbF3, Sb2O3, Sb2Se3, and Sb2Te3; the Y source compound includes one or more of LiCl, LiBr, and LiI.
4. The method for preparing the high entropy lithium argyrodite-type sulfide solid electrolyte according to claim 2, characterized in that: The drying conditions in step 1) are 60-80° C. and vacuum drying for 10-12 h.
5. The method for preparing the high entropy lithium argyrodite-type sulfide solid electrolyte according to claim 2, characterized in that: In the step 2), the mixing after weighing needs to be performed using an agate mortar and ground for 10-20 minutes for mixing.
6. The method for preparing the high entropy lithium argyrodite-type sulfide solid electrolyte according to claim 2, characterized in that: In the step 3), the mixed material precursor is subjected to dry ball milling process, and a high-energy ball mill is used for mixing. The ball mill speed is 400-600 rpm / min, the ball milling time is 8-12 h, the ball-to-material ratio is 20:1, and the mass ratio of large ball milling beads to small ball milling beads is 1:
1.
7. The method for preparing the high entropy lithium argyrodite-type sulfide solid electrolyte according to claim 2, characterized in that: In the step 3), the mixed material precursor is subjected to tableting after ball milling, and the pressure is 200-400 MPa. The diameter of the sheet precursor is 10 mm and the mass is 500-1000 mg.
8. The method for preparing the high entropy lithium argyrodite-type sulfide solid electrolyte according to claim 2, characterized in that: The high temperature treatment process conditions of the flake precursor in step 4) include: heat treatment temperature 400-600°C, heat treatment time 6-8 h, heating rate 1-5°C / min; the cooling rate to room temperature is 10-20°C / min.
9. The use of the high entropy lithium argyrodite-type sulfide solid electrolyte material prepared by the method according to claim 2, characterized in that: The solid electrolyte material is applied to all-solid-state lithium batteries.
10. The use of the high entropy lithium argyrodite-type sulfide solid electrolyte material according to claim 9, characterized in that: The all-solid-state lithium battery comprises a composite positive electrode layer, a sulfide electrolyte layer and a lithium negative electrode / composite negative electrode layer; The composite positive electrode layer and the sulfide electrolyte layer contain the high-entropy lithium argyrodite-type sulfide solid electrolyte material obtained by the above-mentioned preparation process.
Citation Information
Patent Citations
Sulfide solid electrolyte
CN109526242A
Binary co-doped argyrodite type solid electrolyte and preparation and application thereof
CN116154273A
High-entropy sulfide solid electrolyte material and preparation method and application thereof
CN117039135A
Sulfide-based solid electrolyte
CN118020188A
Lithium ion conducting solid material
CN118382602A
Cited By
Method for improving stability of sulfide electrolyte to lithium on large scale
CN119569005A